Answer:
![\boxed{\boxed{\sf x=\frac{23}{10}}\: \sf or \:\boxed{x=2.3}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cboxed%7B%5Csf%20x%3D%5Cfrac%7B23%7D%7B10%7D%7D%5C%3A%20%5Csf%20or%20%5C%3A%5Cboxed%7Bx%3D2.3%7D%7D)
_________________
![\boxed{\sf Step\: By\:Step:- }](https://tex.z-dn.net/?f=%5Cboxed%7B%5Csf%20Step%5C%3A%20By%5C%3AStep%3A-%20%7D)
![\sf 3x-\left(2x-1\right)=7x-\left(3\times \:5x\right)+\left(-x+24\right)](https://tex.z-dn.net/?f=%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D7x-%5Cleft%283%5Ctimes%20%5C%3A5x%5Cright%29%2B%5Cleft%28-x%2B24%5Cright%29)
<u>Remove the parentheses:</u>
![\to\sf 3x-\left(2x-1\right)=7x-3\times \:5x-x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D7x-3%5Ctimes%20%5C%3A5x-x%2B24)
<u>Combine like terms:</u>
![\sf ^*7x-x=6x](https://tex.z-dn.net/?f=%5Csf%20%5E%2A7x-x%3D6x)
![\to\sf 3x-\left(2x-1\right)=6x-3\times \:5x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D6x-3%5Ctimes%20%5C%3A5x%2B24)
<u>Multiply 3 and 5x = 15x:-</u>
![\to\sf 3x-\left(2x-1\right)=6x-15x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D6x-15x%2B24)
<u>Combine like terms:</u>
![\sf ^*6x-15x=-9x](https://tex.z-dn.net/?f=%5Csf%20%5E%2A6x-15x%3D-9x)
![\to\sf 3x-\left(2x-1\right)=-9x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%203x-%5Cleft%282x-1%5Cright%29%3D-9x%2B24)
<u>Expand: 3x-(2x-1)= x+1</u>
![\to\sf x+1=-9x+24](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%2B1%3D-9x%2B24)
<u>Subtract 1 from both sides:</u>
![\to\sf x+1-1=-9x+24-1](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%2B1-1%3D-9x%2B24-1)
![\to\sf x=-9x+23](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%3D-9x%2B23)
<u>Add 9x to both sides:</u>
![\to\sf x+9x=-9x+23+9x](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%2B9x%3D-9x%2B23%2B9x)
![\to\sf 10x=23](https://tex.z-dn.net/?f=%5Cto%5Csf%2010x%3D23)
<u>Divide both sides by 10:</u>
![\to\sf \cfrac{10x}{10}=\cfrac{23}{10}](https://tex.z-dn.net/?f=%5Cto%5Csf%20%5Ccfrac%7B10x%7D%7B10%7D%3D%5Ccfrac%7B23%7D%7B10%7D)
![\to\sf x=\cfrac{23}{10}](https://tex.z-dn.net/?f=%5Cto%5Csf%20x%3D%5Ccfrac%7B23%7D%7B10%7D)
<u>________________________________</u>
Answer:
It is =
Step-by-step explanation:
Because (6 x 1 = 6 ) + 1 x 1/100 = 6.1
The answer for this is n(3+2)
I believe that it is 2x^2+1x-2